Stall identification methods in centrifugal compressor - Mlkvik Marek; Knížat Branislav; Olšiak Róbert (MATEC Web of Conferences, 2023)
The presented paper describes a method for detecting compressor stall precursors in a measured pressure signal using procedures arising from the chaos theory. The experiment was carried out on a scaled-down model of a compressor used in natural gas transportation. It was a single-stage centrifugal compressor with a vane diffuser. The presented method is based on the analysis of an attractor constructed using the time delay method from the pressure signal collected at the compressor outlet flange at a frequency of 25 kHz. Using a parameter called correlation dimension, we identified small changes in the dynamics of the measured signal before the onset of negative stall manifestations. In general, it was found that near the stall curve there were minor disturbances in the flow field in the compressor, due to which the correlation dimension decreased.